1994
DOI: 10.1364/ao.33.002574
|View full text |Cite
|
Sign up to set email alerts
|

Sound in flight: measurement of sound fields by use of TV holography

Abstract: The integrated amplitude and phase distribution of the sound field propagating from sinusoidally vibrating objects in air have been recorded by time-averaged TV holography. The behavior of the sound field is observed in real time by use of dynamic phase modulation. The magnitude and direction of the field are found by acoustic phase stepping and image processing. The field is three dimensional, and recordings of several cross sections are necessary for a complete description, but in many cases valuable informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Optical techniques are both nonintrusive and easily scalable, which make them the preferred choice in many applications. Lökberg 12 and Lökberg et al 13 developed and used phase-modulated TV holography, 14 electro-optic holography, for measurements of sound fields in air radiating from harmonically vibrating objects. Schedin et al [15][16][17] used pulsed holographic interferometry and pulsed TV holography to measure transient sound fields outside impacted plates and beams.…”
Section: Introductionmentioning
confidence: 99%
“…Optical techniques are both nonintrusive and easily scalable, which make them the preferred choice in many applications. Lökberg 12 and Lökberg et al 13 developed and used phase-modulated TV holography, 14 electro-optic holography, for measurements of sound fields in air radiating from harmonically vibrating objects. Schedin et al [15][16][17] used pulsed holographic interferometry and pulsed TV holography to measure transient sound fields outside impacted plates and beams.…”
Section: Introductionmentioning
confidence: 99%
“…It may be possible to solve the problems cited above if estimates can be made of the sound fields by noncontact methods, that is, without introducing a physical probe. Optical sensing [6][7][8][9][10][11][12] is typical of such noncontact methods, in that the noncontact step in obtaining the estimate is to target the sound fields. In 1994, Løkberg used a technique called television holography to estimate the realtime oscillations and phase characteristics of sound fields in air [6].…”
Section: Introductionmentioning
confidence: 99%
“…Optical sensing [6][7][8][9][10][11][12] is typical of such noncontact methods, in that the noncontact step in obtaining the estimate is to target the sound fields. In 1994, Løkberg used a technique called television holography to estimate the realtime oscillations and phase characteristics of sound fields in air [6]. In 1995, Neighbors and colleagues estimated the absolute sound pressure of 0.37-MHz focused sound fields in water by the Schlieren method using CCDs [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having extensively studied refractive index changes induced by airborne acoustic fields emanating from vibrating objects such as loudspeakers using ESPI, 20,21 the Applied Optics Group at the Norwegian University of Science and Technology successfully implemented the observation of underwater acoustic fields using the same technology. 22 In a more specific study, Rustad demonstrated the suitability of ESPI for studying the acoustic field generated by a 3.25 MHz continuous wave medical ultrasound probe, with a spatial resolution of better than 100 m. 23 This technique is, however, limited by the spatial resolution and fixed aspect ratio of the TV camera used to acquire the images and the fact that the sensitivity of the ESPI system is a complex function of the spherical spreading of the optical wave front and target shape and position.…”
Section: Introductionmentioning
confidence: 99%